Economics of reusing spent nuclear fuel by Teplator for district heating applications. (6th December 2021) - Abushamah, Hussein Abdulkareem Saleh; Masata, David; Mueller, Michael; Skoda, Radek
Summary: The Teplator is a nuclear heat‐only reactor under development in the Czech Republic, which uses already irradiated spent nuclear fuel (SNF). This study aims to assess the feasibility of integrating this technology with district heating systems (DHSs) compared with other heating technologies. Therefore, the heating sector in the Czech Republic is evaluated, the need for alternative clean energy sources is explained, and some potential candidate locations for implementing the proposed technology are determined. The availability of the required SNF is investigated. An economic model based on cash flows is developed for evaluating different heat sources. The method includes the essential costs: investment, fuel, operation, maintenance, carbon emission, and additional expenses. The economics of the Teplator is calculated compared with gas, biomass, heat pump, and electric‐based district heating show that Teplator has less expenditure of 55% and 42% than gas boilers and heat pumps. Moreover, 217 kg of CO2 emissions is saved per MWh compared with gas‐based heating. Sensitivity analyses of interest rate, fuel price, construction cost, etc., representing variant scenarios are performed. Although in some cases, for example, when the interest rate is >10%, or 0% salvage value is assumed for Teplator, heat pumps are competitive, Teplator is feasible in many probable scenarios. Abstract : A novel approach of reusing spent nuclear fuel for district heating is proposed and an economic model for evaluating the superiority of this concept compared with the other technologies is formulated. The availability of the spent nuclear fuel reserves is reported confirming the large amount of extractable energy by TEPLATOR technology. The results confirm the competence of this concept encouraging the researchers, energy policymakers and the industrial sector to consider it as an economic carbon‐free solution for district heating.